Is there a consensus on antibiotic usage for dental implant placement in healthy patients?. (25th July 2017) - Park, J; Tennant, M; Walsh, LJ; Kruger, E
Abstract: This systematic review aimed to determine whether there is consensus for antibiotic prescription in healthy patients undergoing implant placement. A search of PubMed, Embase and Medline databases was conducted in January 2016 to find published journal articles on the use of antibiotics in implant placement, according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. The inclusion criteria were prospective human clinical trials investigating antibiotic usage during implant placement. Fifteen studies were deemed suitable. In 13 studies, no statistical difference was found between antibiotic use and the incidence of prosthetic failure, implant failure and early postoperative infections. These were rated as having low to high risk bias. Contrary results were reported in two studies, both of which were rated as having a high potential for bias. In conclusion, antibiotic use in healthy patients for the prophylaxis of surgical infection associated with dental implant placement does not appear to improve clinical outcomes. Practitioners should apply principles of antimicrobial stewardship and not use antibiotics as a routine measure in healthy patients.